Analysis of current variation and solvent flux type on microstructure and hardness of type 304 austenitic stainless steel welded by Tungsten Inert Gas welding - Moh. Syaiful Amri; Mukhlis Mukhlis; Arya Triananda Kusuma (Politeknik Negeri Lhokseumawe, 2022)
Stainless steel is a widely used material in various industries such as aerospace, chemical processing, and transportation. TIG (Tungsten Inert Gas) welding has a low level of productivity compared to other welding processes. This is because the penetration is shallow and the welding efficiency is the lowest. The use of active flux can have an effect on penetration during welding, because active flux is a powder that has an oxide content in it. This study aims to determine the effect of several types of solvents, namely acetone, methanol, and ethanol for the active mixture of TiO2 flux in A-TIG (Actived – Tangsten Inert Gas) welding with a current of 150 A and 200 A on austenite stainless steel type 304 material to depth. penetration, hardness and microstructure in the weld metal, HAZ and Base Metal areas. This research was tested for hardness and metallography. The hardness test resulted that the highest value was found in the variation of solvent ethanol with a current of 200 A, which was 187.14 HVN. The macro results show that the deepest penetration is in the variation of solvent ethanol with a current of 150 A, which is 6.99 mm. The results of the microstructure that occurs in weld metal are in the form of vermicular ferrite and lathy ferrite phases which are caused by low heat input so that the cooling speed is high